Sexual dimorphism of pelvic girdle: pelvimetry and pelvic types in Javanese - Etty Indriati Etty Indriati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: Each population has certain phenotypic traits that are unique compared to other populations. Pelvis's size and morphology are two of them. A western formula of obstetric conjugate = diagonal conjugate - 1.5 to 2.0 em; may not be applicable to Javanese population; and sexual traits in Western pelves may not entirely be the same with Indonesians.Objective: to get a formula for obstetric conjugate, and conduct various pelvic measurements in order to find out the metric pattern as well as the distribution of pelvic types in Javanese.Material and Methods: 27 pelves consisting of 6 females and 21 males housed at the Department of Anatomy, Embryology and Anthropology were studied by connecting the sacrum with the right and left pelvis forming pelvic girdles. Superior inlet, diagonal conjugate, angle of greater sciatic notch, diameter and width of pelves were among the metric studied.Results: Widely used traits such as greater sciatic notch that are used in Western literature to differentiate male and female pelves in Caucasian is not consistent for Javanese pelves. The most consistent skeletal traits for sexing female pelvis are wide subpubic angle (> 75 degree), preauricular sulci, flat posterior pubic symphisis, and short ischiopubic rami. The common type of ginecoyd pelvis in Javanese (48%) is in accord with western pelvis reaching 50%. Compared to the western obstetric conjugate, Javanese obstetric conjugate has a slightly different formula = diagonal conjugate - 1 to 2.6 cm.Conclusions: Several traits in sexual dimorphic of pelvic bone in Javanese do not match with skeletal traits widely used in Western literature, portraying the importance of studying regional human biological variation. The obstetric conjugate of Javanese pelves is not entirely the same with Western formula, though the difference is not significant.Key words: Javanese, pelves, sexual dimorphism, obstetric conjugate